Dobro počutje/subjektivna blaginja sodelavcev kot bistveni dejavnik prehoda v inovativno družbo - Šarotar Žižek, Simona (Organizacija (Kranj), 2009)
The contemporary world is full of contradictions, including the essential problem of well-being of co-workers. Most troubles of this kind cannot be resolved with measures of the usual management and/or economic theory that have caused these troubles. Therefore, the question is raised about what could be done about the well-being of co-workers, if principles and measures of innovative business, social responsibility and requisite holism were used. In the paper the mentioned problem is discussed and a path toward the society of knowledge, innovation and affluence is indicated.
Keywords: podjetja; zaposleni; zadovoljstvo; znanje; knowledge; inovativno poslovanje; inovativno mišljenje; inovativna družba; družbena odgovornost